Meningkatkan Jiwa Kewirausahaan Santri Melalui Analisis Lingkungan di Pondok Pesantren Al usmaniyah - Rahmatullah, Rendy Adetya; Anwar, Muhadjir (Journal Of Human And Education (JAHE), 2024)
Entrepreneurship is an important element that must be explored and developed in facing today's global economy. Al Usmaniyah Islamic Boarding School as a religious educational institution has great potential to develop the entrepreneurial spirit of its students so that they are able to carry out business activities that can increase economic independence. This community service program aims to improve the entrepreneurial spirit of students at Al Usmaniyah Islamic Boarding School, Jombang Regency, through an environmental analysis approach and entrepreneurship training. By using qualitative methods and a participatory approach, this program actively involves students in every stage of the activity, from planning, implementing training, to practical assistance. The SWOT analysis approach is used to help students recognize strengths, weaknesses, opportunities, and threats, both individually and in the context of the Islamic boarding school environment. The results of the program show an increase in students' understanding and skills in the field of entrepreneurship, such as business management, financial management, and marketing strategies. Students also succeeded in designing and implementing small business prototypes that are relevant to the Islamic boarding school environment. Although this program faces obstacles such as time constraints due to the busy Islamic boarding school schedule, the participatory approach has proven effective in encouraging active involvement of students. This program makes a positive contribution to the development of economic independence of students and the Islamic boarding school as a whole. The sustainability of the program is expected through the integration of entrepreneurship training into the routine activities of the Islamic boarding school.